The Importance of Interactive Methods and Principles in English Language Lessons - Ortiqova Musallam Jahongirovna (International Journal on Human-Computing Studies, 2021)
The article investigates the impressions and ideas on the issue "The importance of interactive methods and principles in English language lessons." The use of modern teaching methods leads to high efficiency in the teaching process. It is prudent to choose these methods based on the didactic task of each lesson.Traditionally, methods of teaching foreign languages differentiate between improving and organizational principles. Principles are usually agreed as essential methodological requirements that define the process of education and upbringing.